Role of exhaled hydrogen sulfide in the diagnosis of colorectal cancer - Jian Chen; Yujen Tseng; Peizhun Du; Pengcheng Liu; Huilu Zhang; Guangjian Huang; Cheng’en Hu (BMJ Open Gastroenterology)
Background Colorectal cancer (CRC) is often accompanied by increased excretion of hydrogen sulfide (H2S). This study aimed to explore the value of exhaled H2S in the diagnosis of CRC.Methods A total of 80 people with normal colonoscopy results and 57 patients with CRC were enrolled into the present observational cohort study. Exhaled oral and nasal H2S were detected by Nanocoulomb breath analyser. Results were compared between the two groups. Receiver operating characteristic (ROC) curves were analysed and area under the curves (AUCs) were calculated to assess the diagnostic value of exhaled H2S. Meanwhile, the clinicopathological features, including gender, lesion location and tumour staging of patients with CRC, were also collected and analysed.Results The amount of exhaled H2S from patients with CRC was significantly higher than that of those with normal colonoscopy results. The ROC curve showed an AUC value of 0.73 and 0.71 based on oral and nasal H2S detection, respectively. The exhaled H2S in patients with CRC was correlated with gender, lesion location and tumour progression, including depth of invasion, lymphatic metastasis and TNM (Tumor, Lymph Nodes, Metastasis) staging.Conclusion Exhaled H2S analysis is a convenient and non-invasive detection method for diagnosing CRC, suggesting a potential role in population screening for CRC.